Keakuratan Pemilihan UCoD Kasus Perinatal di Rumah Sakit X Tahun 2024 - Amalia, Rizkiyatul; Aulia, Gaetsa Nurul (Politeknik Negeri Jember, 2024)
In 2023, there were 20 cases of perinatal death at Hospital X. Among these cases, 11 (55%) were reported with UCoD as asphyxia, 6 (30%) as low birth weight, 1 (5%) as anencephaly, 1 (5%) as pulmonary hypoplasia, and 1 (5%) as pulmonary aplasia. According to the perinatal mortality coding rules in ICD-10 volume 2, diagnoses of asphyxia and low birth weight or prematurity cannot be selected as the UCoD. This affects the accuracy of mortality reporting. The aim of this study is to describe the accuracy of UCoD selection in perinatal cases and the use of the Perinatal Mortality Surveillance System (SMPK) at Hospital X in 2024. This study uses a descriptive quantitative approach with a case study method. Data were collected through observations, document reviews, and interviews. The results show that 80% of UCoD selections were inaccurate, while 20% were accurate according to the perinatal mortality coding rules in ICD-10 volume 2. It can be concluded that the inaccuracy in UCoD selection for perinatal cases is due to the lack of proper implementation of mortality coding and the incomplete use of the SMPK.